English-Only Policy and Its Influence on Speaking Skills in Ban E-Lert School Thailand - Devi, Putriana; Maghfiroh, Ana; Harmanto, Bambang; Nimasari, Elok; Chaisiri, Somruethai (Langkawi: Journal of The Association for Arabic and English, 2026)
This study examines the implementation of an English-Only Policy (EOP) in a bilingual program at a Thai junior high school and its impact on students’ English speaking skills. Although EOP has been widely discussed in EFL contexts, limited research has integrated quantitative and qualitative evidence to explain how such policies operate within bilingual secondary classrooms in Thailand. To address this gap, this study employed a mixed-method design involving 30 Grade 1 students at Ban E-Lert School, Loei Province, Thailand. Quantitative data were collected using a one-group pre-test and post-test design assessing fluency, pronunciation, grammatical accuracy, vocabulary mastery, and communication ability, while qualitative data were obtained through structured classroom observations conducted over a 12-week intervention period. Quantitative findings revealed a statistically significant improvement in students’ speaking performance after the implementation of the EOP (t(29) = −10.081, p < .001). Qualitative findings demonstrated increased willingness to communicate in English and reduced reliance on the first language during classroom interaction. However, persistent challenges were also identified, particularly in pronunciation accuracy, limited exposure to appropriate language models, and speaking anxiety during spontaneous communication. This study contributes to the literature by demonstrating that the effectiveness of EOP depends not only on restricting first-language use but also on the provision of pedagogical support, including scaffolding strategies, pronunciation guidance, and constructive feedback. The findings provide insight into how classroom-level language policies interact with instructional practices to support learners’ linguistic and affective development in low-exposure EFL contexts.